Implementation of the District-Wide Mutual Health Insurance Scheme in Ga West Municipality - Ntewusu, D.A. (University of Ghana, 2014)
The National Health Insurance Scheme (NHIS) was introduced in Ghana in 2003. Its main goal was and still is to ensure healthcare access and bridge the inequality gaps in healthcare. Ghana’s NHIS is unique in the sense that it is a hybrid of Social Health Insurance and Community Based Health Insurance schemes. This study is about the implementation of the District-wide Mutual Health Insurance Scheme (DMHIS) in Ga West Municipality. The study is necessitated by the perceived success of the scheme such as increase in enrolment, and utilization of health facilities. Furthermore, there are gaps and challenges which include inadequate medical facilities, escalating cost, and difficulty in reimbursement of providers, which have not only emerged in the process of the implementation of the scheme but have also threatened its sustainability. The study used a mixed methods approach to gather data from a sample of subscribers in Ga West (the seat of the Ga District Scheme), Management and Staff of the Ga scheme and health providers to discuss the implementation process of the scheme. In all, information was gathered from 100 subscribers, 30 healthcare providers, and 30 staff members and management of the Ga scheme. It was found out that community participation, intensive education and special registration exercises, among others were paramount in bringing about the successes chalked by the Ga West scheme whiles inadequate office space, human resources and funding, as well as illiteracy and corruption accounted for the failures of the scheme in Ga West Municipality. The study recommends the development of a comprehensive computerization system that will help in an effective processing of claims to minimize the fraud and corruption associated with the manual system. It is also strongly recommended that more and well trained permanent staff be recruited to ensure a smooth operation of the Ga West Scheme.
Thesis (MPHIL)-University of Ghana, 2014